Global Opportunities to Increase Agricultural Independence Through Phosphorus Recycling. Issue 4 (9th April 2019) - Powers, S. M.; Chowdhury, R. B.; MacDonald, G. K.; Metson, G. S.; Beusen, A. H. W.; Bouwman, A. F.; Hampton, S. E.; Mayer, B. K.; McCrackin, M. L.; Vaccari, D. A.
Abstract: Food production hinges largely upon access to phosphorus (P) fertilizer. Most fertilizer P used in the global agricultural system comes from mining of nonrenewable phosphate rock deposits located within few countries. However, P contained in livestock manure or urban wastes represents a recyclable source of P. To inform development of P recycling technologies and policies, we examined subnational, national, and global spatial patterns for two intersections of land use affording high P recycling potential: (a) manure‐rich cultivated areas and (b) populous cultivated areas. In turn, we examined overlap between P recycling potential and nation‐level P fertilizer import dependency. Populous cultivated areas were less abundant globally than manure‐rich cultivated areas, reflecting greater segregation between crops and people compared to crops and livestock, especially in the Americas. Based on a global hexagonal grid (290‐km 2 grid cell area), disproportionately large shares of subnational "hot spots" for P recycling potential occurred in India, China, Southeast Asia, Europe, and parts of Africa. Outside of China, most of the remaining manure‐rich or populous cultivated areas occurred within nations that had relatively high imports of P fertilizer (net P import:consumption ratios ≥0.4) or substantial increases in fertilizer demand between the 2000s (2002–2006) and 2010s (2010–2014). Manure‐rich cultivated grid cells (those above the 75th percentiles for both manure and cropland extent) represented 12% of the global grid after excluding cropless cells. Annually, the global sum of animal manure P was at least 5 times that contained in human excreta, and among cultivated cells the ratio was frequently higher (median = 8.9). The abundance of potential P recycling hot spots within nations that have depended on fertilizer imports or experienced rising fertilizer demand could prove useful for developing local P sources and maintaining agricultural independence. Key Points: Many nations import mineral phosphorus (P) fertilizers to support agriculture but possess alternative, local, recyclable sources of P in manure and biosolids A global, subnationally resolved analysis revealed where manure‐rich and populous cultivated areas occur and, in turn, where P recycling potential may be high Abundant P recycling opportunities exist in nations that have relied on fertilizer imports or had rising fertilizer demand, and these could be important to future agricultural independence